Tożsamość organizacyjna a kultura organizacyjna - problemy metodologiczne - Sułkowski, Łukasz (Organizational identity and organizational culture - methodological issues, 2006)
The organizational culture is a notion which is very “laden” theoretically and experientially. Organizational culture creates extensive “family of words” which make research difficult ton make. Its obtained results are often disproportionate, and their transfer to the practice meets considerable difficulties. In that case “the identity of the organization” should be a useful term. It is based on the interpretative-symbolical paradigm, with a qualitative and hermeneutical methodology characteristic. In the area of organizational identity it is possible to obtain greater cohesion of the theory and research.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 491-497